High throughput construction of species characterized bacterial biobank for functional bacteria screening: demonstration with GABA-producing bacteria - Qiu, Yanci; Fan, Dingding; Wang, Jianxin; Zhou, Xiaoxue; Teng, Xin; Rao, Chitong (Frontiers in Microbiology, 2025)
Bacteria and their metabolites exhibit remarkable diversity, offering substantial potential for industrial biotechnology. However, the low throughput for constructing and screening bacterial biobanks limits the exploration and utilization of this diversity. In this study, we developed a cost-effective, high-throughput platform for bacterial biobank construction and functional screening. We employed a double-ended barcoding strategy, enabling thousands of bacterial isolates to be pooled for simultaneous Nanopore sequencing of full-length 16S rDNA for species identification. This approach demonstrated 99% accuracy compared to Sanger sequencing while reducing per-sample costs to under 10%. Using this platform, we established a bacterial biobank comprising 15,337 bacterial isolates derived from fermented foods and infant feces collected across China. To identify functional bacteria within the biobank, we designed a versatile fluorescence-based biosensor system employing dual plasmids to decouple metabolite sensing from signal reporting. This modular biosensor framework can be readily adapted for detecting diverse metabolites. As a proof-of-concept, we screened 1,740 isolates and identified 46 with high γ-aminobutyric acid (GABA)-producing capacity, demonstrating potential for probiotic development. Together, our integrated bacterial identification and functional screening platform provides an efficient pipeline for the discovery of functional bacteria, advancing industrial biotechnology through synthetic biology.